Evaluation of a Cape Town Safety Intervention as a Model for Good Practice: A Partnership between Researchers, Community and Implementing Agency. Issue 1 (5th May 2015) - Cassidy, Tali; Ntshingwa, Melikaya; Galuszka, Jakub; Matzopoulos, Richard
VPUU has a wealth of experience to share and is engaged with broader national and international policymakers and implementing agencies. Researchers are grappling with the difficulty of providing a rigorous project evaluation for these collaborations which could identify project elements that work with a view to their replication. This paper traces the evolution of an evidence-based approach to violence prevention in the Western Cape Province of South Africa. The Violence Prevention through Urban Upgrading (VPUU) project in Cape Town uses such an approach, and relies on a 'whole-of-society' methodology as well. The project and the difficulty of its evaluation are discussed. A partnership between VPUU, researchers, the community and local government has revealed both opportunities and obstacles, which are the subjects of a case study described here.